eDNA metabarcoding of decapod crustaceans across Indonesian seas has implications for biodiversity conservation and fisheries sustainability - Madduppa, Hawis; Sani, Lalu M. Iqbal; Nugroho, Kuncoro Catur; Bengen, Dietriech G.; Muchlisin, Zainal Abidin; Fadli, Nur; Subhan, Beginer; Arafat, Dondy; Zamani, Neviaty P.; Sunuddin, Adriani; Ismet, Meutia Samira; Srimariana, Endang S.; et al. (Frontiers in Marine Science, 2022)
Environmental DNA (eDNA) methods are increasingly viewed as alternate or complementary approaches to conventional capture-based surveys for marine conservation and fisheries management purposes, especially at large spatial scales in mega-biodiversity regions such as Indonesia. Decapod crustacean distribution and diversity across Indonesia are still poorly known, even for economically important fisheries commodities. This study assessed coral reef associated decapod diversity and distribution by sampling 40 sites in three regions (West, Central, East), representing 17 provinces and 10 Fisheries Management Areas (FMAs) across Indonesia, with a special focus on the blue swimming crab Portunus pelagicus. DNA sequencing (Illumina iSeq100) data were analysed in mBRAVE (Multiplex Barcode Research And Visualization Environment) yielded 406 OTUs belonging to 32 families, with 47 genera and 51 species identified. The number of families identified was highest in the Central region (25), while the most genera (31) and species (36) were identified in the West region. Alpha diversity did not differ significantly between regions or provinces, while Beta diversity differed significantly between provinces but not between regions. Our results also showed 31 species are possibility native based on the distribution meanwhile 12 species do not appear to have been recorded based of SeaLifeBase or WorMS. While providing a reference for further exploration of Indonesian coastal and small island decapod biodiversity, the high proportion of unidentified taxa calls for concerted efforts to develop and maintain reference specimen and sequence repositories and expand species conservation status assessments. The economically important decapod crustaceans identified in this study included three crabs (Charybdis anisodon, Charybdis japonica, Portunus pelagicus), a freshwater prawn (Macrobrachium nipponense), a lobster (Panulirus stimpsoni) and two penaeid shrimps (Mierspenaeopsis hardwickii and Trachysalambria aspera). For most decapod taxa, observed patterns indicate management under existing provincial and/or FMA level management structures is appropriate. Furthermore, the data can inform science-based fisheries management strategies, in particular for P. pelagicus.